1998
DOI: 10.1246/bcsj.71.1597
|View full text |Cite
|
Sign up to set email alerts
|

High Complexation Ability of Thiacalixarene with Transition Metal Ions. The Effects of Replacing Methylene Bridges of Tetra(p-t-butyl)calix[4]arenetetrol by Epithio Groups

Abstract: The ability of tetra(p-t-butyl)tetrathiacalix[4]arenetetrol (TCA, H4L), a cyclic tetramer of p-(t-butyl)phenol bridged with four epithio groups, to bind metal ions was investigated via a solvent extraction study. Although tetra(p-t-butyl)calix[4]arenetetrol (CA) has very poor affinity for transition metal ions (M2+), TCA is an excellent extractant of these metal ions. The chemical formulae of the extracted TCA metal complexes were found by slope analysis to be neutral 1 : 1 complexes [MH2L]. The origin of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(45 citation statements)
references
References 19 publications
4
40
0
1
Order By: Relevance
“…It could be determined from Figures 3-5 that the extracted species of Cs(I) and Sr(II) with SC4A are Cs¨SC4A and Sr¨2SC4A, respectively, the extraction equilibrium of Sr(II) is similar to that reported in the literature [35], and can be expressed as follows:…”
Section: Dependence Of Extraction On Temperaturesupporting
confidence: 71%
See 1 more Smart Citation
“…It could be determined from Figures 3-5 that the extracted species of Cs(I) and Sr(II) with SC4A are Cs¨SC4A and Sr¨2SC4A, respectively, the extraction equilibrium of Sr(II) is similar to that reported in the literature [35], and can be expressed as follows:…”
Section: Dependence Of Extraction On Temperaturesupporting
confidence: 71%
“…Therefore, increasing the operation temperature in the experimental conditions adversely affected the extraction. It could be determined from Figures 3-5 that the extracted species of Cs(I) and Sr(II) with SC4A are Cs•SC4A and Sr•2SC4A, respectively, the extraction equilibrium of Sr(II) is similar to that reported in the literature [35], and can be expressed as follows: (4) where H4L and Sr•2H3L are free SC4A and Sr-SC4A complex.…”
Section: Dependence Of Extraction On Temperaturesupporting
confidence: 69%
“…The separation of the MA from Ln is, however, a diffi cult chemical separation to achieve as there are minor differences in the chemical properties of these elements. Studies in recent years have shown that ligands containing soft donor atoms such as N and S offer a higher probability of being more selective for An(III) elements (Kikuchi et al, 2004, Zhu, 1995, Modolo et al, 1998b, Wei et al, 2000a, Iki et al, 1998, Morohashi et al, 2001, Mathur et al, 2001. Although the exact mechanism for this preferential complexing behavior has not been entirely elucidated, many researchers are investigating the merits of using soft donor ligands in solid-phase extraction to perform An(III) separations from Ln(III) elements in high level liquid waste (HLLW) solutions subsequent to upstream removal of U and Pu.…”
Section: Separation Of An(iii) From Ln(iii) Elementsmentioning
confidence: 99%
“…1, б) [18]. Верхній вінець макроциклу містить чотири аніонні сульфонатні угруповання, котрі забезпечують гарну водорозчинність тіакаліксарену та адгезію до протеїнових молекул за рахунок електростатич них контактів із позитивно зарядженими атома ми азоту амінокислотних фрагментів [19].…”
Section: +unclassified